The Influence of Social Media Influencers and the Role of E-Commerce on the Purchase Decision of Cosmetic Products Through Import Activities - Nabila, Salima Ananda; Saputera, Denny (Journal Research of Social Science, Economics, and Management, 2025)
This study investigates the influence of social media influencers and the role of e-commerce on purchasing decisions of imported cosmetic products, with a specific focus on university students in West Java. The research is motivated by the increasing penetration of digital platforms in shaping consumer behavior within the beauty industry, where imported cosmetics continue to dominate due to their global reputation, quality assurance, and trend-driven innovations. Using a quantitative associative approach, data were collected through online questionnaires and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that social media influencers significantly affect cosmetic import activity but do not directly influence purchase decisions. Conversely, e-commerce platforms demonstrate a positive and significant role in shaping purchasing decisions, though their direct effect on cosmetic imports remains insignificant. Furthermore, purchase decisions were found to positively and significantly impact cosmetic import activity, underscoring the central role of consumer behavior in driving import volumes. These results highlight that while influencers effectively stimulate awareness and interest, their impact is more indirect, whereas e-commerce provides convenience and access that strongly encourage purchase intentions. For policymakers and cosmetic industry stakeholders, these insights emphasize the need to optimize influencer strategies and e-commerce features in order to strengthen consumer engagement and ensure sustainable import growth. Academically, the research contributes to expanding literature on digital marketing, consumer behavior, and international trade by bridging gaps in prior studies that have rarely addressed official cosmetic imports in the Indonesian context.